Nanoheterostructure Ag2S/CdS/ZnO and Bi2S3/Ag2S/ZnO for Solar Photoelectrochemical Cells - Zainal, Zulkarnain; Holi, Araa Mebdir; Al-zahrani, Asla Abdullah (Universiti Malaysia Terengganu, 2024)
Nanoheterostructure materials comprising metal oxides and chalcogenides are extensively studied in the pursuit of clean, low-cost, sustainable, and renewable energy generation. Photoelectrochemical (PEC) cells with zinc oxide nanorods (ZnO NRs)-based photoanodes are considered among the most promising approaches for solar-to-chemical energy conversion. The efficiency of the nanorods can be further enhanced by inorganic sensitisation using narrow-gap metal sulfides (such as Ag₂S, CdS, and Bi₂S3). To showcase these capabilities, two stable novel ternary nanoheterostructured photoelectrodes, Ag₂S/CdS/ZnO NRs and Bi₂S₃/Ag₂S/ZnO NRs were fabricated using facile hydrothermal and successive ionic layer adsorption and reaction (SILAR) techniques. High-resolution transmission electron microscopy (HRTEM) revealed the formation of well-distributed and highly uniform nanosized metal sulfide particles along the ZnO nanorods. The materials' energy gaps exhibited a significant shift, with enhanced light absorption in the visible region. The photoelectrochemical efficiency increased dramatically, with a 15-fold enhancement for Ag₂S/CdS/ZnO NRs and a 13-fold enhancement for Bi₂S₃/Ag₂S/ZnO NRs compared to pristine ZnO NRs. These electrodes show great potential for use in photoelectrochemical solar cells and solar hydrogen generation.